Mapping presentations of crafts in the Danish heritage industry: Deliberations on research design and preliminary findings - Bill, Josefine (FormAkademisk, 2023)
In this paper, I present the methodological and theoretical deliberations behind a mapping of how crafts are presented in the Danish cultural heritage industry. I trace the historical background of crafts in the Danish heritage industry and present definitions of key concepts such as ‘craft’ and ‘the Danish heritage industry’. I then develop a research design consisting of a questionnaire and ethnographic fieldwork. I consider how research questions about scope and variation can be operationalized in the questionnaire and how theoretical perspectives from critical heritage studies (Smith, 2006) and vital materialism (Bennett, 2010; 2012) can inform the questionnaire and fieldwork. Finally, some preliminary findings are presented along with some comments on the use of questionnaires in heritage research.